A prospective study on the relevance of crush or squash cytology of central nervous system lesions, in the present-day surgery - Singh, Roma; Saproo, Nipun (International Journal of Advances in Medicine, 2022)
Background: The intra-operative cytology in the evaluation of central nervous system (CNS) lesions is a simple and rapid technique, and a useful tool. There is not much literature available on the value of crush cytology during the operation. The current study was planned to assess the feasibility and efficacy of intra-operative squash cytology as standalone method in the rapid intra-operative diagnosis of intracranial tumor. Methods: A prospective observational study was carried out in the department of neurology in collaboration with department of pathology, Medanta: The Medicity, Gurugram, for a period of six months from January 2019 to June 2019, on randomly selected 60 patients, aged: 18 years and above. Two to three tissue bits, from different sites of the mass, were taken to prepare squash cytology smear. Results: Out of 60 patients operated, 54 had neoplastic and 6 had non-neoplastic lesions. Neoplastic benign lesions were observed in 41 patients and neoplastic malignant lesions were diagnosed in 13 patients. There was 17.67% offering a wrong diagnosis on crush cytology. Out of the 13 cases of meningioma, there was a discrepancy in 3 (three) cases. Conclusions: Crush cytology is a useful adjunct to the diagnosis in neurosurgical practice. This study suggests and confirms the reliability of squash cytology, but further multicentre studies with larger number of patients may help to decide its use in clinical practice.